Knowledge, experiences, and practices of women affected by female genital schistosomiasis in rural Madagascar: A qualitative study on disease perception, health impairment and social impact. - Angela Schuster; Bodo Sahondra Randrianasolo; Oliva Onintsoa Rabozakandraina; Charles Emile Ramarokoto; Dorthe Brønnum; Hermann Feldmeier (Public Library of Science (PLoS), 2022)
Background Female genital schistosomiasis (FGS) is a neglected manifestation of urogenital schistosomiasis caused by S. haematobium. The disease presents with symptoms such as pelvic pain, vaginal discharge and bleeding and menstruation disorders, and might lead to infertility and pregnancy complications. The perspectives of women with FGS have not been studied systematically. The aim of the study was to understand knowledge, experiences, and practices of women with FGS. Methods We performed a qualitative study with seventy-six women diagnosed of having FGS, in the Ambanja district in Northwest Madagascar. Data collection was either through focus group discussion (N = 60) or in an individual semi-structured interview (N = 16). FGS was diagnosed by colposcopy. The data was analysed using Mayring´s qualitative content analysis. Results Knowledge on how the disease is acquired varied and ideas on prevention remained vague. Patients suffered from vaginal discharge and pelvic complaints. Some women expressed unbearable pain during sexual intercourse and compared their pain to an open wound being touched. FGS considerably impaired women´s daily activities and their quality of life. Infertility led to resignation and despair, conflicts with the partner and to social exclusion from the community. Women fearing to sexually transmit FGS refrained from partnership and sexual relations. Many women with FGS reported stigmatisation. A coping strategy was to share strain with other women having similar complaints. However, concealing FGS was a common behaviour which led to social isolation and delayed health care seeking. Conclusions Our study underlines that FGS has an important impact on the sexual health of women and on their social life in the community. Our results highlight the importance of providing adequate health education and structural interventions, such as the supply of water and the provision of sanitation measures. Further, correct diagnosis and treatment of FGS in adolescent girls and women should be available in all S. haematobium-endemic areas. Trial registration The qualitative study was embedded in a randomised controlled trial (RCT) in which two doses of praziquantel were compared (https://clinicaltrials.gov/ct2/show/NCT04115072).